Metabolit Darah Domba yang Disuplementasi Bakteri Pendegradasi HCN dan Sulfur Pada Pakan Mengandung Tepung Daun Singkong Pahit (Manihot glaziovii) - Sri Suharti; Annitsa Shofiyana; Asep Sudarman (Buletin Ilmu Makanan Ternak, 2017)
This research was aimed to analize blood profiles and metabolites of sheep fed bitter cassava leaves (Manihot glaziovii) meal supplemented with cyanide degrading bacteria and sulphur. The research used 15 local male sheeps (Garut), with average of aged 7-9 month and body weight 21.45 ± 3.33 kg. The sheep are placed in individual cages and kept for90 days. The experimental design was a block randomized design with 3 treatments and 5 replicates. The treatments were P1 = control (40% napier grass : 30% cassava leaves meal : 30% concentrate), P2 = P1 + cyanide degrading bacterial, and P3 = P2 + sulphur. Variables served were leukocyte, erythrocyte, haematokrit, haemoglobin, monocyte, basophil, limphocyte, neutrophil, eosinophil, neutrophil limphocyte ration, glucose, protein total, albumin, and triglyceride of blood. Data were analyzed by using analysis of variance. Any significant differences were further tested using Duncan Multiple Range Test. The results showed that cyanide degrading bacteria and sulphur supplementation did not affectblood profiles and metabolites of sheep, except eosinophil proportion. The used of cyanide degrading bacteria or its combination with sulphur to the sheep fed ration contain bitter cassava leaf meal very significantly decreased (P<0.01) eosinophil proportion. In conclution, cyanide degrading bacteria and sulfur supplementation to the sheep fed ration contain bitter cassava leaves meal did not alter blood profiles and metabolites, but could improved body defense in the toxic detoxification.Key words: blood profiles, blood metabolite, cassava leaf, cyanide degrading bacteria, sheep